2005
DOI: 10.12968/bjon.2005.14.14.18556
|View full text |Cite
|
Sign up to set email alerts
|

The value of the role of the rehabilitation assistant

Abstract: This article outlines the experiences of nursing and therapy staff regarding the introduction of rehabilitation assistants. The authors discuss issues concerning a role (the rehabilitation assistant) that was created after staff identified that therapeutic input (nursing, physiotherapy, occupational therapy, speech and language therapies), which was provided from Monday to Friday, was not continued over weekend periods. A small-scale audit was carried out to assess the role and the efficacy of the rehabilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Therapy assistants provided assistance to allied health professionals, and spent time on different program delivery such as individual therapy, group therapy, administration duties, and health promotion. Similar findings were reported by Pullenayegum et al following a small scale audit to assess the role and effectiveness of rehabilitation assistants 18. The assistants operated only on weekends to maintain the rehabilitation process over a seven-day period.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Therapy assistants provided assistance to allied health professionals, and spent time on different program delivery such as individual therapy, group therapy, administration duties, and health promotion. Similar findings were reported by Pullenayegum et al following a small scale audit to assess the role and effectiveness of rehabilitation assistants 18. The assistants operated only on weekends to maintain the rehabilitation process over a seven-day period.…”
Section: Resultssupporting
confidence: 84%
“…Rehabilitation assistants, on the other hand, saw their role mainly as being organized to offer patients a more continuous, holistic and patient-focused service while at the same time allowing health professionals extra time to carry out more complex tasks. Similarly, the results of an evaluation conducted by Pullenayegum et al demonstrated the valuable contribution of rehabilitation assistants in providing consistent and goal-directed rehabilitation to patients who received treatment from a multidisciplinary team 18. Improved communication and interdisciplinary working between nurses, therapists, and rehabilitation assistants has created a well-coordinated and integrated approach to rehabilitation.…”
Section: Benefits Of Introducing Ahas Within the Allied Health Workforcementioning
confidence: 98%
“…A key finding was the role of support workers in providing emotional support to clients and the potential for this element of their role to have a significant influence on patient well-being. There were numerous studies that demonstrated that service users perceive support workers as vital to their recovery through provision of emotional and practical support, advocacy and companionship [7,9,20,[37][38][39][40][41][42][43][44][45].…”
Section: The Companionmentioning
confidence: 99%
“…They are also perceived to be an economically effective way to deliver 'safe and skilled' care while enabling the professional workforce to 'upskill' to provide more specialist services [3]. The support worker role is therefore seen as pivotal to enabling professionals to carry out more complex tasks [4][5][6][7] by maintaining or even increasing the capacity of care previously delivered by professionally qualified practitioners [7][8][9]. Support workers have therefore been a focus of recent health workforce reform in the UK with policies targeting growth in numbers [2,10] and expansion of their roles.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The vocational qualifications of the AHA, which combines generic academic core modules and work-based learning, allows the AHA to have a broad spectrum of knowledge and skills necessary to prepare them for work with patients, carers and the relevant professionals or specialists. 14 Published research has highlighted numerous benefits of AHAs that include serving as a link across disciplines within a multi-disciplinary team, 15 the ability to work with patients to provide support, supervision and monitoring of their progress, 16 the ability to provide consistent and goal directed rehabilitation 17 and improvements in patient compliance and patient clinical outcomes. 18 The rapidly expanding area of telerehabilitation, i.e.…”
Section: Introductionmentioning
confidence: 99%